Rare case of hypertension in pregnancy in rural setup - neurofibromatosis in pregnancy: a case report - Limbu, Adarsh (Journal of General Practice and Emergency Medicine of Nepal, 2025)
A 23-year-old woman, pregnant with her first child at 15 weeks, came in with severe headaches and dangerously high blood pressure (220/130 mmHg). Despite initial treatment with labetalol, her blood pressure remained unstable, even after adding methyldopa and nifedipine. During her exam, signs of Neurofibromatosis type 1 (NF1) were evident, including multiple neurofibromas, café-au-lait spots, and axillary freckling. Due to limited resources, tests for secondary causes of hypertension, like renovascular disease or pheochromocytoma, could not be performed. The patient chose not to be referred to a higher-level facility, citing financial concerns, and opted for voluntary discharge. Later, she delivered a premature baby at 34 weeks via cesarean section at a different hospital. While NF1 itself doesn’t directly increase maternal mortality, it complicates the management of hypertension in pregnancy, contributing to a higher risk of adverse outcomes for both mother and baby. In rural areas with limited healthcare resources, these challenges are even more pronounced, and patient preferences can further complicate care. This case highlights the urgent need to improve access to healthcare, especially in rural settings, and to provide better training for healthcare providers managing complex pregnancies.